Detection of infection with hydatid cysts in abattoirs animals at Kirkuk governorate, Iraq - Raid Sabah Radhwan; Fatima Shihab Al-Nasiri (Tikrit Journal of Pure Science, 2021)
During the period from September 2020 to February 2021, the current study was conducted to determine the total prevalence of infection with hydatid cysts disease in the various organs (especially liver, lung, spleen, kidney, heart, and mesentery) of abattoirs animals (sheep, cattle, goats and buffaloes) in Kirkuk governorate and its suburbs. Visual examination and hand-feeling were used to detect and identify the site of infection with hydatid cysts, as well as a microscopic examination was used to determine the fertility of hydatid cysts.